2019
DOI: 10.1093/pm/pnz014
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Pain Inhibitory Function: Endurance-Trained Athletes vs Active Controls

Abstract: Objective Athletes are at risk for developing chronic pain conditions, but the role of exercise in the modulation of pain in athletes has not been well established. The aim of this study was to investigate conditioned pain modulation (CPM) and exercise-induced hypoalgesia (EIH) responses between 13 endurance-trained athletes and 13 normally active controls. Methods In a cross-sectional, nonrandomized study with two independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…[CPM]), and functional performance capacity (VO2-max) in endurance-trained athletes and normally active controls [26]. This is in contrast to the current study which found an association between improvement in physical performance capacity and improvement in EIH.…”
Section: A C C E P T E D a U T H O R M A N U S C R I P Tcontrasting
confidence: 99%
See 1 more Smart Citation
“…[CPM]), and functional performance capacity (VO2-max) in endurance-trained athletes and normally active controls [26]. This is in contrast to the current study which found an association between improvement in physical performance capacity and improvement in EIH.…”
Section: A C C E P T E D a U T H O R M A N U S C R I P Tcontrasting
confidence: 99%
“…Furthermore, EIH has been utilized as a predictive factor for pain progression following total knee replacement [18] and exercise therapy [20] in knee osteoarthritis patients, and lower EIH has been reported in physically inactive individuals compared with physically active people [21,22]. This indicates EIH subgroup differences in relation to physical performance capacity and that exercise or an active lifestyle (enhanced physical performance capacity) may improve EIH although cross-sectional studies have found conflicting evidence in healthy subjects [14,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of moderate and vigorous physical activity have been found to be associated with a greater magnitude of EIH in older healthy adults [46], but no relationship with EIH in younger adults [47]. It has been suggested that a U-shaped relationship exists between activity and pain where too little and too much physical activity may lead to chronic pain [48]. Our results support a U-shaped relationship but only for isometric exercise: high levels of activity predicted impaired EIH, moderate levels predicted EIH, and low levels showed a trend for impaired EIH (although this was non-significant).…”
Section: Prediction Of Eihmentioning
confidence: 99%
“…7 Furthermore, a few studies have addressed self-reported psychological variables, such as pain catastrophizing and kinesiophobia. 6,8 However, these have yielded either null-findings or inconclusive evidence. 6,[9][10][11] Concurrently, recent research indicates that cognitive function might affect pain, and in particular, pain inhibition.…”
Section: Introductionmentioning
confidence: 99%